Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
This Selected Issues paper analyzes Russia's growth performance, the recovery in output, factors behind the post-crisis recovery, the role of the ruble depreciation and higher international energy prices, and labor market trends. The paper describes the developments in the government budget since the August 1998 crisis, determinants of revenue performance, recent tax reform, and the outstanding structural issues in the fiscal sector. It also provides a statistical appendix and annexes regarding the changes in the exchange system and the external trade regime, 1999-2000.